A Culturally Tailored Diabetes Self-Management Intervention Incorporating Race-Congruent Peer Support to Address Beliefs, Medication Adherence and Diabetes Control in African Americans: A Pilot Feasibility Study - Shiyanbola OO; Maurer M; Schwerer L; Sarkarati N; Wen MJ; Salihu EY; Nordin J; Xiong P; Egbujor UM; Williams SD (Patient Preference and Adherence, 2022)
Olayinka O Shiyanbola,1 Martha Maurer,2 Luke Schwerer,3 Nassim Sarkarati,3 Meng-Jung Wen,1 Ejura Y Salihu,1 Jenna Nordin,3 Phanary Xiong,3 Ugboaku Maryann Egbujor,3 Sharon D Williams4 1Division of Social and Administrative Sciences, University of Wisconsin School of Pharmacy, Madison, WI, USA; 2Sonderegger Research Center, University of Wisconsin School of Pharmacy, Madison, WI, USA; 3University of Wisconsin School of Pharmacy, Madison, WI, USA; 4University of Wisconsin School of Medicine and Public Health, Milwaukee, WI, USACorrespondence: Olayinka O Shiyanbola, Division of Social and Administrative Sciences, School of Pharmacy, University of Wisconsin-Madison, 777 Highland Avenue, Madison, WI, 53705, USA, Email Olayinka.Shiyanbola@wisc.eduIntroduction: Current diabetes self-management programs are often insufficient to improve outcomes for African Americans because of a limited focus on medication adherence and addressing culturally influenced beliefs about diabetes and medicines. This study evaluated the feasibility and acceptability of a novel culturally tailored diabetes self-management intervention that addressed key psychosocial and sociocultural barriers to medication adherence for African Americans.Methods: The intervention consisted of group education and race-congruent peer-based phone support. Three African Americans who were engaged in taking their diabetes medicines (ambassadors), were matched with 8 African Americans who were not engaged in taking medicines (buddies). We conducted a single group, pre/post study design with African Americans with type 2 diabetes. Wilcoxon signed rank tests assessed mean score differences in outcomes at baseline compared with 6-months follow-up. Semi-structured interviews explored buddies’ acceptability of the intervention.Results: Buddies and ambassadors were similar in age and mostly female. Recruitment rates were 80% for buddies and 100% for ambassadors. Retention rate for primary outcomes was 75%. Buddies had a mean completion of 13.4/17 of sessions and phone calls. Ambassadors completed 84% of intervention calls with buddies. Although there were no statistically significant differences in mean A1C and medication adherence, we found a clinically meaningful decrease (− 0.7) in mean A1C at the 6-month follow up compared to baseline. Secondary outcomes showed signal of changes. Themes showed buddies perceived an improvement in provider communication, learned goal setting strategies, and developed motivation, and confidence for self-management. Buddies perceived the program as acceptable and culturally appropriate.Conclusion: This culturally tailored diabetes self-management intervention that addresses diabetes self-management, psychosocial and behavioral barriers to medication adherence, and incorporates race-congruent peer support from African Americans engaged in taking medicines seemed feasible and acceptable. The results provide support for a fully powered randomized trial to test the intervention’s efficacy.Trial Registration: https://clinicaltrials.gov/ct2/show/NCT04857411.Date of Registration: April 23, 2021.Keywords: African Americans, diabetes self-management, peer support, health beliefs, medication adherence